(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article presents an analysis of modern approaches to ensuring the security of digital wallets in hybrid mobile applications. The main focus is on biometric authentication, including such methods as fingerprint and face recognition. A comparative analysis of its advantages and integration with traditional security methods is conducted. It is noted that the use of biometrics significantly reduces the number of unauthorized transactions and increases convenience for users.